Insurgent love: abolition and domestic homicide - Whynacht, Ardath (Fernwood Publishing, 2021)
"Domestic homicide is violence that strikes within our most intimate relations. The most common strategy for addressing this kind of transgression relies on policing and prisons. But through examining commonly accepted typologies of high-risk intimate partner violence, Ardath Whynacht shows that policing can be understood as part of the same root problem as the violence it seeks to mend and provides an abolitionist frame for the most dangerous forms of intimate partner violence. This book illustrates that the origins of both the carceral state and toxic masculinity are situated in settler colonialism and racial capitalism and sees police homicide and domestic homicide as akin. Describing an experience of domestic homicide in her community and providing a deeply personal analysis of some of the most recent cases of homicide in Canada, the author inhabits the complexity of seeking abolitionist justice. Insurgent Love traces the major risk factors for domestic homicide within the structures of racial capitalism and suggests transformative, anti-capitalist, anti-racist, feminist approaches for safety, prevention and justice."--